INVESTIGATION OF THE STATE OF CATEGORICAL AND CONCEPTUAL APPARATUS OF PUBLIC ADMINISTRATION MECHANISMS IN THE FIELD OF CIVIL PROTECTION - Poteryaiko S.P., (Pressing Problems of Public Administration, 2017)
The paper raises the issue of insufficient level of research into the essence of public administrationmechanisms in the field of civil protection. On the basis of the previous scientific studies, theauthor’s definitions of the concepts of “public administration mechanisms” and “public administrationmechanisms in the field of civil protection” are proposed.